2018
DOI: 10.7717/peerj.5842
|View full text |Cite
|
Sign up to set email alerts
|

Chronological age, biological age, and individual variation in the stress response in the European starling: a follow-up study

Abstract: The strength of the avian stress response declines with age. A recently published study of European starlings (Sturnus vulgaris) found that a marker of biological age predicted the strength of the stress response even in individuals of the same chronological age. Specifically, birds that had experienced greater developmental telomere attrition (DTA) showed a lower peak corticosterone (CORT) response to an acute stressor, and more rapid recovery of CORT levels towards baseline. Here, we performed a follow-up st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Third, we investigated the direct effects of developmental treatments (the amount of food and the level of begging effort) on impulsivity in the current cohort of birds. Although the two previous starling studies (Bateson et al 2015; Nettle et al 2015a), in line with evidence from other systems (Lovic et al 2011; Brydges et al 2015), found no direct effects of developmental treatments on impulsivity, in the present cohort of starlings, there is other evidence for direct treatment effects on adult behavioural phenotype (Neville et al 2017; Gott et al 2018). This may be because the developmental treatments in the current birds, who were hand-reared, were better controlled than earlier cross-fostering manipulations.…”
Section: Introductionsupporting
confidence: 85%
“…Third, we investigated the direct effects of developmental treatments (the amount of food and the level of begging effort) on impulsivity in the current cohort of birds. Although the two previous starling studies (Bateson et al 2015; Nettle et al 2015a), in line with evidence from other systems (Lovic et al 2011; Brydges et al 2015), found no direct effects of developmental treatments on impulsivity, in the present cohort of starlings, there is other evidence for direct treatment effects on adult behavioural phenotype (Neville et al 2017; Gott et al 2018). This may be because the developmental treatments in the current birds, who were hand-reared, were better controlled than earlier cross-fostering manipulations.…”
Section: Introductionsupporting
confidence: 85%
“…In terms of biological stressors, factors such as animal handling, restraint, transportation and injury have all been shown to activate the HPA axis (Bosson, Palme & Boonstra 2013;Dehnhard et al 2001;Ganswindt et al 2010;Goymann et al 1999;Hämäläinen et al 2014). However, individual variation, in terms of the neuroendocrine response to the presence of a stressor, can vary considerably and should be taken into account when using a biological stressor for assay validation (see Gott et al 2018;Koolhaas et al 2010). The physiological validation is conducted through the artificial activation of the HPA axis; this is achieved by injecting an individual with synthetic adrenocorticotropic hormone (ACTH) to increase GC production (ACTH challenge; Palme 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CORT profiles were measured from the same 31 birds when they were aged 127–134 days (methods described in Gott et al 2018; the data used here are ‘age point 1’ from that study as this is the closest in age to the judgement bias experiment). Briefly, we used a standardised capture-handling-restraint protocol employed previously in European starlings (Andrews et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The three judgement bias variables were correlated with each of baseline CORT, peak CORT and ΔCORT. Correlations involving peak CORT were partial, controlling for baseline CORT, and correlations involving ΔCORT were partial, controlling for CORT at 15 min (see Gott et al 2018). An alpha level of significance of P  < 0.05 was used throughout.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation